Economic regulation and cost-efficiency in Brazilian urban public transport: The case of Belo Horizonte - Alexandre de Ávila Gomide (Institute for Applied Economic Research (ipea), 2015)
The transport economics literature has indicated that introduction of competition for the market in urban bus services (i.e. by means of competitive bidding) could promote cost-efficiency with low fares and better quality services. Therefore, this paper analyse the main outcomes and the latest consequences of the bidding process occurred during 1997-1998 in Belo Horizonte with the use of operational data. Did economic efficiency improve? Did fares decrease? This case study concludes that contracting-out bus services through a bidding process is not enough to ensure company cost-efficiency if public authorities do not implement a well-devised competitive tendering process and do not design an effective regulatory framework. We hope that this study can help policy makers to improve future bidding processes in Brazilian cities and to design an effective regulatory model for the urban bus sector, especially in these days where the media have made known the critical situation endured by the urban poor, which have no conditions to afford the costly fare levels of the public transport services.
Keywords: R48; L92; 330